Effect of Various Barley Steeping Conditions on the Content of Albuminous Substances in the Malt - Rostovskaya Marina F.; Boyarova Margarita D.; Klykov Alexey G. (Техника и технология пищевых производств)
Introduction. Malt production requires low-protein barley. Unfortunately, bad environmental conditions often lead to higher protein content than specified in the related standards. The research objective was to study the effect of barley steeping conditions on the level of albuminous substances in malt and to assess the possibility of reducing nitrogenous substances by changing the steeping regime. Study objects and methods. The research featured two varieties of barely, namely “Primorsky 89” and “Primorsky 98”. Both varieties were harvested in 2013, 2015, and 2016 in the Primorye Region of Russia. The protein content in the grain of each variety differed significantly, depending on the year of harvest, and ranged from 1.75% to 2.5%. Two micromalting modes differed only in the steeping time and were performed at 17°C. The malt samples were analyzed for total protein content, total soluble nitrogen, Kolbach Index, and free amino nitrogen. Results and discussion. The “Primorsky 89” variety proved insensitive to a longer steeping time, thus maintaining the same characteristics of the malt. The decrease in the protein level in the malt compared to the raw material was approximately the same for each mode and amounted to 0.3%. The Kolbach Index ranged between 30.31% and 35.1%. The experiment failed to produce the desired degree of dissolution, while the difference in this indicator under various modes was less than 1%. The long steeping mode proved optimal for the “Primorsky 98” variety. An increase in the steeping time made it possible to reduce the content of nitrogenous substances in the malt by 1%, compared to the raw material. Higher initial protein content in the grain resulted in lower content of nitrogenous substances during malting. The long steeping mode also resulted lowered the Kolbach Index by 3%: it was 34.7% – 39.5% for the long steeping mode and 31.1–36.8% for the short steeping mode. Conclusion. The barley variety and the malting method affected the dynamics of nitrogenous substances. For some varieties, a longer steeping period proved to reduce the content of nitrogenous substances in the malt and increase the Kolbach Index.